Coated paper
The coated paper with PHBH and polyvinyl alcohol resin layers addresses coating defects and hot water resistance issues, providing enhanced durability and biodegradability.
Patent Information
- Application Number
- JP2023097194
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
AI Technical Summary
Coated paper using PHBH resin is prone to coating defects such as cracks and pinholes, and lacks sufficient hot water resistance, which is crucial for paper cups holding hot beverages.
A coated paper design with an undercoating layer containing PHBH, an inorganic pigment, and an adhesive, and a top coating layer using a polyvinyl alcohol resin with a saponification degree of 90% or more, enhances hot water resistance and prevents softening.
The coated paper maintains strength and water resistance at various temperatures, ensuring safety and rapid biodegradability, suitable for paper cups and other applications.
Smart Images

Figure 2024178782000001 
Figure 2024178782000002 
Figure 2024178782000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated paper coated with a coating liquid containing PHBH. [Background technology]
[0002] In recent years, efforts have begun to prevent environmental destruction caused by plastic waste, and there is a demand to replace disposable plastic products with materials that have a smaller impact on the environment. Alternative materials to plastic include biodegradable plastics, wood, paper, etc. Coated paper, which is paper coated with a resin, can perform various functions depending on the resin used. However, if the resin used is derived from fossil resources or is non-biodegradable, the environmental impact reduction effect of using paper is lost. Therefore, there is a demand for coated paper in which a paper base material is coated with an aqueous dispersion of biodegradable plastic. Aliphatic polyesters such as polylactic acid and polycaprolactone are known as biodegradable plastics. However, aliphatic polyesters have the problem that they take a long time to biodegrade at low temperatures and decompose slowly in natural environments such as the ocean.
[0003] On the other hand, poly(3-hydroxybutyrate) resins are thermoplastics produced by microorganisms that are highly degradable under both aerobic and anaerobic conditions, and have the remarkable ability to be decomposed by microorganisms in a short period of time even in water, such as the ocean. Patent Document 1 describes that a biodegradable polyester aqueous dispersion containing PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)), a copolymer of 3-hydroxybutyrate and 3-hydroxyhexanoate, has excellent film-forming properties and gives a resin coating film that is flexible, stretchable, and resistant to bending when applied to paints, adhesives, fiber processing, sheet / film processing, paper processing, etc. However, a coating layer coated with an aqueous dispersion of PHBH is prone to coating defects such as cracks and pinholes. Therefore, Patent Document 2 proposes mixing PHBH and an adhesive in a solids weight ratio of 99.9 / 0.1 to 60.0 / 40.0 and coating the mixture. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2004 / 041936 [Patent Document 2] Patent Publication No. 2021-195717 Summary of the Invention [Problem to be solved by the invention]
[0005] The inventors of the present invention have studied the water resistance of paper cup base paper using PHBH and PVA for the undercoating layer and PHBH for the top coating layer, with reference to the prior art. As a result, it was confirmed that the coated surface, which is the liquid-contacting side, has no problem with water resistance against cold liquids or liquids at room temperature. On the other hand, because paper cups may be used to hold hot beverages such as tea and coffee, the inventors evaluated the paper by bringing hot water into contact with the coated surface, which is the liquid-contacting side, and discovered that the hot water gradually penetrates from the surface in contact with the hot water, causing the paper to become wet. Paper cups often contain heated beverages such as tea, coffee, and soup, and moisture can have a significant effect on gripping the cup, so the base paper for paper cups must be resistant to hot water. The present invention has been developed against this background, and an object of the present invention is to provide a coated paper having a PHBH coating layer that maintains good warm water resistance and is resistant to soggyness. [Means for solving the problem]
[0006] The means for solving the problems of the present invention are as follows. 1. A paper substrate having, on at least one surface thereof, an undercoating layer containing PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)), an inorganic pigment, and an adhesive, and a top coating layer containing PHBH; The adhesive contains a polyvinyl alcohol resin having a saponification degree of 90% or more, The Cobb water absorption of 90°C hot water after 30 minutes of contact is 25g / m 2 A coated paper characterized in that: 2. The coated paper according to 1., characterized in that the degree of polymerization of the polyvinyl alcohol resin is 250 or more and 3,000 or less. 3. The coated paper according to 1 or 2, wherein the polyvinyl alcohol resin has a hydrophobic group. 4. The coated paper according to 3., wherein the undercoating layer contains 0.1 to 60 parts by weight of the adhesive per 100 parts by weight of the total of the PHBH and the inorganic pigment. Effect of the Invention
[0007] The coated paper of the present invention has excellent water resistance to low to high temperature water. The coated paper of the present invention can maintain its strength even when in contact with low to high temperature water, and is therefore particularly safe when hot water is placed in it. The coated paper of the present invention has a high ratio of biodegradable materials to the entire coated paper, and therefore, even if it is leaked into the environment, it will decompose quickly. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The coated paper of the present invention has, on at least one surface of a paper substrate, an undercoating layer containing PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)), an inorganic pigment, and an adhesive, and a top coating layer containing PHBH; The adhesive contains a polyvinyl alcohol resin having a saponification degree of 90% or more, The Cobb water absorption of 90°C hot water after 30 minutes of contact is 25g / m 2 The following is the result. In this specification, the expression "A to B" (A and B are numerical values) means a numerical range including A and B, that is, "A or more and B or less."
[0009] (Paper base material) The paper base material is a sheet (hereinafter also referred to as "base paper") mainly made of pulp, and is obtained by papermaking a paper stock that further contains fillers, various auxiliaries, and the like. Examples of pulp include chemical pulps such as bleached hardwood kraft pulp (LBKP), bleached softwood kraft pulp (NBKP), unbleached hardwood kraft pulp (LUKP), unbleached softwood pulp (NUKP), sulfite pulp, and other mechanical pulps, stone-ground pulp, thermomechanical pulp, and other wood fibers such as deinked pulp and waste paper pulp, and non-wood fibers obtained from kenaf, bamboo, hemp, and other materials, and one or more of these can be used in appropriate combination. Among these, it is preferable to use chemical pulp of wood fiber or mechanical pulp of wood fiber, and it is more preferable to use chemical pulp of wood fiber, for reasons such as the fact that foreign matter is unlikely to be mixed into the paper base material, that discoloration is unlikely to occur over time when recycled as waste paper raw material, that the surface texture is good when printed due to its high whiteness, and that its value in use is particularly high when used as a packaging material. Specifically, the blending amount of wood fiber chemical pulp such as LBKP or NBKP relative to the total pulp is preferably 80% by weight or more, more preferably 90% by weight or more, even more preferably 95% by weight or more, and most preferably 100% by weight.
[0010] Examples of fillers that can be used include inorganic fillers such as talc, kaolin, calcined kaolin, clay, heavy calcium carbonate, light calcium carbonate, white carbon, zeolite, magnesium carbonate, barium carbonate, titanium dioxide, zinc oxide, silicon oxide, amorphous silica, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide, barium sulfate, and calcium sulfate, and organic fillers such as urea-formalin resin, polystyrene resin, phenolic resin, and hollow microparticles. Note that fillers are not essential materials and may not be used.
[0011] Examples of various auxiliary agents include sizing agents such as rosin, alkyl ketene dimer (AKD), alkenyl succinic anhydride (ASA), polyacrylamide polymers, polyvinyl alcohol polymers, cationic starch, various modified starches, urea-formaldehyde resin, melamine-formaldehyde resin, and other dry strength agents, wet strength agents, retention agents, drainage improvers, coagulants, aluminum sulfate, bulking agents, dyes, fluorescent brighteners, pH adjusters, defoamers, UV inhibitors, anti-fading agents, pitch control agents, slime control agents, and the like, and can be selected and used as appropriate as needed.
[0012] The surface of the paper substrate may be treated with various chemicals. Examples of chemicals include oxidized starch, hydroxyethyl etherified starch, enzyme-modified starch, polyacrylamide, polyvinyl alcohol, surface sizing agents, water-resistant agents, water retention agents, thickeners, and lubricants, and these may be used alone or in combination of two or more. Furthermore, these various chemicals may be used in combination with pigments. Examples of pigments include inorganic pigments such as kaolin, clay, engineered kaolin, delaminated clay, heavy calcium carbonate, light calcium carbonate, mica, talc, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicate salts, colloidal silica, and satin white, and organic pigments such as solid, hollow, and core-shell types may be used alone or in combination of two or more.
[0013] The basis weight of the paper base material can be selected appropriately depending on the desired quality and its application, but is usually 20 g / m 2 More than 600g / m 2 Less than 25 g / m is preferred. 2 More than 600g / m 2 The following is more preferred: For example, when used for wrapping paper, paper bags, lids, lining paper, packaging materials for liquid paper containers such as milk cartons, posters to be used outdoors, etc., the basis weight of the paper base material is 20 g / m 2 More than 350g / m 2 When used as a flexible packaging material, the paper base material preferably has a basis weight of 20 g / m 2 More than 100g / m 2 Less than 20 g / m is preferable. 2 More than 80g / m 2 The following is more preferable. The soft packaging material is, among the packaging materials, particularly, a material having a density of 20 g / m 2 From 100g / m 2 It is a flexible packaging material made of thin paper of about 150 g / m2. When used for paper cups, paper containers, paper boxes, paper plates, paper trays, etc., the basis weight of the paper base material is 150 g / m2. 2 More than 300g / m 2 The following is preferred: The density of the paper base material can be appropriately selected depending on the desired qualities and ease of handling, but is usually 0.5 g / cm 3 More than 1.0g / cm 3 The following are preferred:
[0014] The method of manufacturing (papermaking) the paper base material is not particularly limited, and known manufacturing (papermaking) methods and papermaking machines can be selected, such as a Fourdrinier papermaking machine, a cylinder papermaking machine, a short wire papermaking machine, a twin-wire papermaking machine such as a gap former type or a hybrid former type (on-top former type). The pH during papermaking may be in the acidic range (acidic papermaking), pseudo-neutral range (pseudo-neutral papermaking), neutral range (neutral papermaking), or alkaline range (alkaline papermaking), and after papermaking in the acidic range, an alkaline agent may be applied to the surface of the paper layer. The paper base material may be one layer, or may be composed of two or more layers. Furthermore, when treating the surface of a paper substrate with a chemical, the method of surface treatment is not particularly limited, and known coating devices such as a rod metering size press, a pond type size press, a gate roll coater, a spray coater, a blade coater, or a curtain coater can be used.
[0015] (Undercoating layer) The undercoating layer contains PHBH, an inorganic pigment, and an adhesive. In addition to PHBH, an inorganic pigment, and an adhesive, the undercoating layer may contain various auxiliaries that are blended in coating solutions in the papermaking field, such as other biodegradable resins (e.g., polybutylene succinate, polycaprolactone, polylactic acid, etc.), dispersants, viscosity modifiers, water retention agents, defoamers, water resistance agents, fluorescent dyes, coloring dyes, coloring pigments, surfactants, pH adjusters, cationic resins, anionic resins, ultraviolet absorbers, and metal salts, as necessary.
[0016] <phbh> PHBH is a copolymer of 3-hydroxybutyrate (hereinafter also referred to as 3HB) and 3-hydroxyhexanoate (hereinafter also referred to as 3HH), and is a biodegradable resin known to be produced by microorganisms. In the present invention, the PHBH used may be derived from microorganisms or petroleum resources, but it is preferable to use the PHBH derived from microorganisms in terms of reducing the environmental load.
[0017] Microorganisms that produce PHBH are not particularly limited as long as they accumulate PHBH intracellularly, but examples include bacteria of the genus Alcaligenes, such as A. lipolytica, A. eutrophus, and A. latus, as well as bacteria of the genus Pseudomonas, Bacillus, Azotobacter, Nocardia, and Aeromonas. Among them, in terms of productivity of PHBH, strains such as Aeromonas caviae, and Alcaligenes eutrophus AC32 into which genes of PHA synthase group have been introduced (Accession No. FERM BP-6038, Date of deposit on August 7, 1997, National Institute of Advanced Industrial Science and Technology, International Patent Organism Depositary, Address: Central 6, 1-1-1 Higashi, Tsukuba-shi, Ibaraki-ken, Japan) (J. Bacteriol., 179, pp. 4821-4830 (1997)) are particularly preferred. A method for obtaining PHBH from Aeromonas caviae, a microorganism of the Aeromonas genus, is disclosed, for example, in Japanese Patent Application Laid-Open No. 05-093049. These microorganisms are used by culturing them under appropriate conditions to accumulate PHBH in the cells. The carbon source and culture conditions used in the culture can be obtained according to the methods described in JP-A-05-093049, JP-A-2001-340078, etc., but are not limited thereto.
[0018] The composition ratio (mol%) of PHBH is preferably 3HB:3HH=97:3 to 75:25, more preferably 95:5 to 85:15. If the composition of 3HH is less than 3 mol%, the properties of PHBH become similar to those of 3HB homopolymer, resulting in loss of flexibility and an excessively high film-forming processing temperature, which is undesirable. If the composition of 3HH exceeds 25 mol%, the crystallization rate becomes too slow to be suitable for film-forming processing, and the degree of crystallization decreases, making the resin flexible and decreasing the bending modulus. The composition ratio of PHBH can be measured by centrifuging the aqueous dispersion and then drying the powder obtained by NMR analysis. Microbial PHBH is a random copolymer. To adjust the molar ratio of the copolymer, there are several methods, such as selecting the bacterial cells, selecting the carbon source as the raw material, blending with PHBH of different molar ratios, and blending with 3HB homopolymer.
[0019] The weight-average molecular weight of PHBH is preferably 50,000 to 1,500,000. When the weight-average molecular weight of PHBH is within this range, it is possible to form a film at a low temperature when drying after coating. The weight-average molecular weight of PHBH is more preferably 100,000 to 500,000, and even more preferably 150,000 to 450,000. The weight-average molecular weight of PHBH can be determined by gel permeation chromatography (GPC, such as "Shodex GPC-101" manufactured by Showa Denko K.K.) using polystyrene gel (such as "Shodex K-804" manufactured by Showa Denko K.K.) in a column, using chloroform as the mobile phase, and converting it into a polystyrene-equivalent molecular weight. The measurement sample is a powder obtained by centrifuging an aqueous dispersion containing PHBH and then drying it.
[0020] The average particle size of PHBH is preferably 0.1 to 50 μm. PHBH with an average particle size of less than 0.1 μm is difficult to produce by microbial production, and even when obtained by chemical synthesis, a microparticulation operation is required. If the average particle size exceeds 50 μm, uneven coating may occur on the surface when a coating liquid containing PHBH is applied. The average particle size of PHBH is more preferably 0.5 to 10 μm. The average particle size of PHBH refers to the particle size corresponding to 50% accumulation of all particles in a normal distribution when a water suspension of PHBH is adjusted to a predetermined concentration using a general-purpose particle sizer such as a Microtrack particle sizer (manufactured by Nikkiso, FRA). The solid content of PHBH in the coating liquid is not particularly limited and can be adjusted to a viscosity suitable for the coating method, but is preferably 5 to 70% by weight. If the solid content is less than 5% by weight, the coating film tends not to be formed well, and if it exceeds 70% by weight, the viscosity of the coating liquid becomes too high, making coating difficult. The solid content of PHBH in the coating liquid is more preferably 10 to 55% by weight.
[0021] <Inorganic pigments> As the inorganic pigment, those used for coating on paper can be used without any particular limitation, and examples thereof include kaolin, clay, engineered kaolin, delaminated clay, heavy calcium carbonate, light calcium carbonate, mica, talc, bentonite, titanium dioxide, barium sulfate, calcium sulfate, zinc oxide, silicic acid, silicate salts, colloidal silica, satin white, etc., and one or more of these can be used. Among these, one or more of kaolin, heavy calcium carbonate, light calcium carbonate, mica, talc, and bentonite are preferred.
[0022] The inorganic pigment preferably has a volume 50% average particle size (D50) (hereinafter also referred to as "average particle size") of 7.0 μm or less in terms of oil resistance and water resistance when a top coating layer is provided on the under coating layer. The average particle size of the inorganic pigment is more preferably 6.0 μm or less, even more preferably 5.0 μm or less, even more preferably 4.5 μm or less, and even more preferably 4.0 μm or less. There is no particular lower limit to the average particle size of the inorganic pigment, but from the viewpoint of dispersibility, for example, it is preferably 0.1 μm or more, and more preferably 0.2 μm or more. When two or more inorganic pigments are included, it is preferable that the average particle size of at least one of the inorganic pigments is within the above-mentioned numerical range, and the ratio of the inorganic pigments satisfying this average particle size to the total inorganic pigments is preferably 50% by weight or more, and more preferably 70% by weight or more.
[0023] The inorganic pigment preferably has an aspect ratio of 60 or less in terms of oil resistance and water resistance when a top coating layer is provided on the under coating layer. The aspect ratio of the inorganic pigment is more preferably 40 or less, even more preferably 30 or less, even more preferably 25 or less, and even more preferably 20 or less. There is no particular lower limit to the aspect ratio of the inorganic pigment. When two or more inorganic pigments are included, it is preferable that the aspect ratio of at least one of them is within the above-mentioned numerical range, and the proportion of the inorganic pigment satisfying this aspect ratio to the total inorganic pigments is preferably 50% by weight or more, more preferably 70% by weight or more.
[0024] <Adhesive> The adhesive bonds the PHBH, inorganic pigment, paper base material, etc. In the coated paper of the present invention, since the undercoating layer contains an adhesive, it is possible to obtain a uniform undercoating layer in which coating defects such as cracks and pinholes are suppressed. The adhesive contains a polyvinyl alcohol resin having a saponification degree of 90% or more. The polyvinyl alcohol resin may have a saponification degree of 90% or more, and one or more of the following may be used: polyvinyl alcohol, acetoacetylated polyvinyl alcohol, carboxy-modified polyvinyl alcohol, amide-modified polyvinyl alcohol, sulfonic acid-modified polyvinyl alcohol, butyral-modified polyvinyl alcohol, olefin-modified polyvinyl alcohol, nitrile-modified polyvinyl alcohol, pyrrolidone-modified polyvinyl alcohol, silicone-modified polyvinyl alcohol, other modified polyvinyl alcohol, and ethylene-vinyl alcohol copolymer. Among these, polyvinyl alcohol resins having hydrophobic groups are preferred from the viewpoint of water resistance. Examples of polyvinyl alcohol resins having hydrophobic groups include butyral-modified polyvinyl alcohol, olefin-modified polyvinyl alcohol, and nitrile-modified polyvinyl alcohol, and one or more of these may be used. Among these, olefin-modified polyvinyl alcohol is preferred. Examples of the α-olefin in the olefin-modified polyvinyl alcohol include ethylene, propylene, isobutylene, 1-butene, 1-pentene, and 1-hexene, with ethylene being preferred.
[0025] The saponification degree of the polyvinyl alcohol resin having a saponification degree of 90% or more is preferably 92% or more, more preferably 94% or more, even more preferably 96% or more, and even more preferably 97% or more. The polymerization degree of the polyvinyl alcohol resin having a saponification degree of 90% or more is preferably 250 or more and 3000 or less, more preferably 300 or more, and even more preferably 400 or more, and is more preferably 2700 or less, even more preferably 2400 or less, and even more preferably 2000 or less.
[0026] The adhesive may include, in addition to polyvinyl alcohol resins having a saponification degree of 90% or more, one or more selected from polyvinyl alcohol resins having a saponification degree of less than 90%, starches such as oxidized starch, etherified starch, and esterified starch, cellulose derivatives such as hydroxymethylcellulose, hydroxyethylcellulose, methylcellulose, ethylcellulose, carboxymethylcellulose, acetylcellulose, and nanocellulose, partially saponified ethylene-vinyl acetate copolymers, styrene-butadiene copolymer latex, conjugated diene polymer latex of methyl methacrylate-butadiene copolymer, acrylic polymer latex, styrene-maleic anhydride copolymer latex, polyvinyl chloride latex, polyvinyl acetate latex, etc. However, the ratio of polyvinyl alcohol resins having a saponification degree of 90% or more to the total amount of the adhesive is preferably 50% by weight or more, more preferably 70% by weight or more, even more preferably 90% by weight or more, even more preferably 95% by weight or more, even more preferably 98% by weight or more, and even more preferably 99% by weight or more.
[0027] The solids weight ratio of PHBH to inorganic pigment in the undercoating layer (PHBH: inorganic pigment) is preferably 85:15 to 0.01:99.99. Although the mechanism is unclear, the adhesion of the obtained undercoating layer is improved by further blending inorganic pigment into a coating liquid containing PHBH and an adhesive. The solids weight ratio of PHBH to inorganic pigment (PHBH: inorganic pigment) is more preferably 65:35 to 5:95, and even more preferably 45:55 to 25:75. In particular, when the average particle size of the inorganic pigment exceeds 7.0 μm, the solids weight ratio of PHBH to inorganic pigment (PHBH: inorganic pigment) is more preferably 65:35 to 40:60, and even more preferably 55:45 to 45:55. The total ratio of PHBH and inorganic pigment to the total solid content of the coating layer is preferably 60% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more.
[0028] The undercoating layer preferably contains 0.1 to 60 parts by weight of an adhesive per 100 parts by weight of the total of PHBH and inorganic pigment. If the adhesive content is less than 0.1 part by weight, the adhesive may not be able to exert its effect of improving fixation, whereas if it exceeds 60 parts by weight, water resistance may be insufficient. When the adhesive contains a polyvinyl alcohol-based resin having a hydrophobic group with a saponification degree of 90% or more, the content of the adhesive relative to 100 parts by weight of the total of PHBH and inorganic pigment is more preferably 1 part by weight or more, even more preferably 2 parts by weight or more, and more preferably 50 parts by weight or less, even more preferably 40 parts by weight or less. When the adhesive does not contain a polyvinyl alcohol-based resin having a hydrophobic group with a saponification degree of 90% or more, the content of the adhesive relative to 100 parts by weight of the total of PHBH and the inorganic pigment is more preferably 1 part by weight or more, even more preferably 2 parts by weight or more, and more preferably 30 parts by weight or less, even more preferably 25 parts by weight or less, and even more preferably 20 parts by weight or less.
[0029] (Top coating layer) In the coated paper of the present invention, a top coating layer containing PHBH can be formed on the under coating layer. By forming a top coating layer on an under coating layer containing an inorganic pigment, the heat seal strength is improved. This is presumably because inorganic pigments have better thermal conductivity than PHBH and adhesives, so the under coating layer containing inorganic pigments reaches high temperatures in a short time, and the top coating layer is exposed to high temperatures for a longer time during heat fusion processing.
[0030] The top coating layer may contain the same PHBH as above except for the range of the weight average molecular weight, and the PHBH of the top coating layer preferably has a weight average molecular weight of 50,000 to 1,500,000. The PHBH of the top coating layer preferably has a weight-average molecular weight greater than that of the under-coating layer. The higher the molecular weight of PHBH, the smaller the MFR and the higher temperature required for heat sealing. However, since the top coating layer of the present invention has excellent heat sealing properties, a high molecular weight PHBH can also be suitably used. Furthermore, the top coating layer contains PHBH with a large weight-average molecular weight, which allows the oil resistance, water resistance, and other properties derived from PHBH to be more effectively exhibited.
[0031] The top coating layer preferably contains 50% by weight or more of PHBH, more preferably 70% by weight or more, even more preferably 90% by weight or more, even more preferably 95% by weight or more, even more preferably 98% by weight or more, and even more preferably 99% by weight or more. In addition to PHBH, the top coating layer may contain various auxiliaries that are blended in coating solutions in the papermaking field, such as other biodegradable resins such as polybutylene succinate, polycaprolactone, and polylactic acid, adhesives, inorganic pigments, dispersants, viscosity improvers, water retention agents, defoamers, water resistance agents, fluorescent dyes, coloring dyes, coloring pigments, surfactants, pH adjusters, cationic resins, anionic resins, ultraviolet absorbers, metal salts, lubricants, and water repellents, as necessary.
[0032] (Coating of undercoating layer and top coating layer) In the present invention, the coating method of the undercoating layer and the top coating layer is not particularly limited, and they can be coated using a known coating device and coating system. For example, the coating device may be a blade coater, a bar coater, a roll coater, an air knife coater, a reverse roll coater, a curtain coater, a spray coater, a size press coater, a gate roll coater, etc. In addition, the coating system may be an aqueous coating using a solvent such as water, or a solvent coating using a solvent such as an organic solvent, etc., and the aqueous coating is preferred. The undercoating layer and the top coating layer can be dried by any of the usual methods, such as using a steam heater, a gas heater, an infrared heater, an electric heater, a hot air heater, a microwave, or a cylinder dryer. The top coating layer can be applied simultaneously with the undercoating layer, before the undercoating layer is dried, or after the undercoating layer is dried.
[0033] The coating weight of the undercoat layer is 1g / m2 in dry weight. 2 More than 50g / m 2 The coating weight of the undercoating layer is preferably 1 g / m or less. 2 If the thickness is less than 50 g / m, the effect of the undercoating layer may be almost negligible. 2 If it is more than this amount, the drying load during coating will be large. The coating weight of the undercoating layer is 3g / m 2 More preferably, 5 g / m 2 More preferably, 40 g / m 2 Less than 30 g / m is more preferable. 2 The following is even more preferred:
[0034] The coating weight of the top coating layer is 0.5 g / m 2 More than 20g / m 2 The coating weight of the top coating layer is preferably 0.5 g / m or less. 2 If the thickness is less than 20 g / m, the effect of the top coating layer may be almost negligible. 2 If the amount is more than this, the drying load during coating will be large. The coating amount of the top coating layer is 1g / m 2 More preferably, 3 g / m 2 More preferably, 17 g / m 2 Less than 14 g / m is more preferable. 2 The following is even more preferred:
[0035] Coated paper The coated paper of the present invention has a Cobb water absorbency of 25 g / m2 in hot water at 90°C after a contact time of 30 minutes (hereinafter also referred to as Cobb water absorbency (90°C)). 2 The Cobb water absorbency (90°C) is a value measured in accordance with "Paper and paperboard - Water absorbency test method - Cobb method" specified in JIS P 8140:1998 under conditions of 90°C water and a contact time of 30 minutes. The coated paper of the present invention has a Cobb water absorbency (90°C) value of 22 g / m 2 Less than 19 g / m is preferred 2 Less than 16 g / m is more preferable. 2 More preferably, 13 g / m 2 Even more preferably, 10 g / m 2 Even more preferred is the following:
[0036] In the coated paper of the present invention, since the under-coating layer and the top-coating layer contain PHBH, the functionality of PHBH can be exhibited, and the paper can be used, for example, as a heat seal layer, an oil-resistant layer, a water-resistant layer, etc. The under-coating layer can be provided on only one side or both sides of the paper substrate. When the under-coating layer is provided on both sides, the top-coating layer can be provided on one under-coating layer or on both under-coating layers.
[0037] The heat seal layer is a layer having heat sealing suitability, specifically, a layer that can be bonded to an object by heating and pressing. An oil-resistant layer is a layer whose average kit number measured at any five points on the layer surface is 4 or more in accordance with "Paper and paperboard - Oil repellency test method - Kit method" specified in J.TAPPI No.41:2000. The water-resistant layer is a layer that has a Cobb water absorbency of 20 g / m2 or more when exposed to water at 23°C for 30 minutes, in accordance with JIS P 8140:1998 "Paper and paperboard - Water absorption test method - Cobb method". 2 The layers are as follows: Cobb water absorption (23°C) is 10g / m 2 Less than 5 g / m is preferable. 2 Less than 3 g / m is more preferable. 2 More preferably, 2 g / m 2 Even more preferred is the following:
[0038] The coated paper of the present invention is easy to mold, maintain its shape, and ensure airtightness, and can therefore be suitably used for paper bags, paper containers, paper boxes, paper cups, (soft) packaging materials, lid materials, and the like. The coated paper of the present invention, in which the coating layer is a heat seal layer, can be suitably used as wrapping paper, paper containers, paper boxes, paper cups, (soft) packaging materials, paper plates, paper trays, etc. The coated paper of the present invention, in which the coating layer is both a heat-sealing layer and an oil-resistant layer, can be suitably used as (soft) packaging materials or wrapping paper for foods that contain a lot of oil, such as hamburgers, hot dogs, French fries, fried chicken, potato chips, etc., paper linings for fried foods such as tempura, paper plates, paper trays, paper cups, etc. EXAMPLES
[0039] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples, parts and % are by weight, respectively, unless otherwise specified.
[0040] Inorganic pigments Kaolin: Shiraishi Kogyosha, KCS, average particle size 3.6 μm, aspect ratio 10 to 15 ·PHBH According to the method described in Patent Document 1, an aqueous dispersion of PHBH having a solid content concentration of 50% by weight and a weight-average molecular weight of 600,000 was obtained. ·glue PVA1: Kuraray Co., Ltd., 5-88, saponification degree 88 mol%, polymerization degree 500 PVA2: Kuraray Co., Ltd., 22-88, saponification degree 88 mol%, polymerization degree 1700 PVA3: Kuraray Co., Ltd., 60-98, saponification degree 98 mol%, polymerization degree 2400 PVA4: Kuraray Co., Ltd., 28-98, saponification degree 98 mol%, polymerization degree 1700 PVA5: Kuraray Co., Ltd., 5-98, saponification degree 98 mol%, polymerization degree 500 PVA6: Kuraray Co., Ltd., 3-98, saponification degree 98 mol%, polymerization degree 300 Olefin modified PVA 1: Kuraray Co., Ltd., RS-2117 (ethylene modified PVA), saponification degree 98 mol%, polymerization degree 1700 Olefin-modified PVA 2: Kuraray Co., Ltd., HR-3010 (ethylene-modified PVA), saponification degree 99 mol%, polymerization degree 1000
[0041] (Evaluation method) Pinhole test (blue water) A piece of paper measuring 5cm x 10cm was prepared and placed on a table with the coated side facing up. A cotton swab soaked in blue water (brilliant blue dye solution: surface tension: 29.6mN / m) was run in a zigzag pattern over the entire coated surface, and after leaving it for 30 seconds, the number of stained spots (pinholes) was visually counted. The test was carried out three times, and the average value was evaluated according to the following criteria. [Evaluation Criteria] ○: Average number of pinholes is 0 ○△: The average number of pinholes is more than 0 and less than 10. △: The average number of pinholes is more than 10. ×: Not pinholes (dots), but seeps in entirely.
[0042] Heat sealability Two square test pieces with sides of 100 mm were cut from the resulting coated paper, and the coating layers were placed in contact with each other and pressed at a pressure of 130°C and 2 kgf / cm. 2 The heat seal was performed with pressure applied for 1 second. The heat-sealed test piece was peeled off by hand, and the peeled part was visually observed and the heat sealability was evaluated according to the following criteria. If the evaluation was good or fair, there was no problem in practical use. [Evaluation Criteria] ◯: Peeling occurs within the paper base (paper base is destroyed). Δ: Most of the peeling occurs within the paper base (paper base is destroyed). ×: Peeling occurs between the coating layers.
[0043] Water, hot water Cobb water absorption test The test was conducted in accordance with JIS P8140:1998, with 23°C or 90°C water and a contact time of 30 minutes. Note that the 90°C water is not maintained at the same temperature during the test, but gradually loses heat and becomes cold. In addition, the Cobb water absorption test was not conducted for products that were rated "X" in the pinhole test (blue water). Paper stiffness The stiffness of the paper after the Cobb water absorption test was evaluated according to the following criteria. [Evaluation Criteria] 〇: No soggy △: A little soggy ×: Wet
[0044] [Examples 1 to 9, Comparative Examples 1 to 10] Inorganic pigment, PHBH, and adhesive were added so as to obtain the solid content weight ratios shown in Tables 1 and 2, and water was further added and stirred to obtain a coating liquid for an under layer having a solid content concentration of 40% by weight. Water was added to PHBH and stirred to obtain a coating liquid for a top layer having a solid content concentration of 40% by weight. Paper base material (basis weight 220g / m 2 The undercoat layer coating liquid was applied onto one side of the paper and dried at 105° C. for 1 minute. The top layer coating liquid was then applied onto the other side and dried at 160° C. for 3 minutes to obtain a coated paper having an undercoat layer and a top coat layer. The coated papers thus obtained were subjected to the above-mentioned evaluation tests, and the results are shown in Tables 1 and 2.
[0045] [Table 1]
[0046] [Table 2]
[0047] It was confirmed that by using PVA with a saponification degree of 90% or more as an adhesive, coated paper with excellent water resistance in hot water at 90°C can be obtained.
[0048] [Examples 10 to 14, Comparative Examples 11 to 13] An inorganic pigment, PHBH, and adhesive were added so as to obtain the solid content weight ratio shown in Table 3, and water was further added and stirred to obtain an underlayer coating liquid with a solid content concentration of 40% by weight. Water was added to PHBH and stirred to obtain a top layer coating liquid with a solid content concentration of 40% by weight. Paper base material (basis weight 220g / m 2 The undercoat layer coating liquid was applied onto one side of the paper and dried at 105° C. for 1 minute. The top layer coating liquid was then applied onto the other side and dried at 160° C. for 3 minutes to obtain a coated paper having an undercoat layer and a top coat layer. The coated paper thus obtained was subjected to the above-mentioned evaluation tests, and the results are shown in Table 3.
[0049] [Table 3]
[0050] By including olefin-modified PVA as an adhesive, the material had excellent water resistance in hot water over a wider range of adhesive blend ratios.< / phbh>
Claims
1. On at least one surface of a paper substrate, there is provided an undercoating layer containing PHBH (poly(3-hydroxybutyrate-co-3-hydroxyhexanoate)), an inorganic pigment, and an adhesive, and a top coating layer containing PHBH; The adhesive contains a polyvinyl alcohol-based resin having a saponification degree of 90% or more, The Cobb water absorption of 90°C hot water after 30 minutes of contact is 25 g / m 2 A coated paper characterized in that:
2. 2. The coated paper according to claim 1, characterized in that the degree of polymerization of the polyvinyl alcohol resin is 250 or more and 3,000 or less.
3. 3. The coated paper according to claim 1, wherein the polyvinyl alcohol resin has a hydrophobic group.
4. 4. The coated paper according to claim 3, wherein the undercoating layer contains 0.1 to 60 parts by weight of the adhesive per 100 parts by weight of the total of the PHBH and the inorganic pigment.
Citation Information
Patent Citations
Coated paper
JP2021195717A
Aqueous dispersion of biodegradable polyester and method for production thereof
WO2004041936A1
Cited By
Laminated piezoelectric element and electroacoustic transducer
US12323763B2
